Three-sphere swimmer in two dimensions at low Reynolds number condition - A. Sheikhshoaei; M. Rajabi (مهندسی مکانیک شریف, 2022)
Being widely ubiquitous in fluidic mediums from aquatic environments to bodies, for the sake of their mobility, microorganisms, such as bacteria and motile cells, make use of particular swimming strategies that are counter-intuitive to that of our daily life experience, given that the physics governing micrometer is different from that of macroscale physics. Living in this particular realm of supposedly zero Reynolds number, these microscopic creatures are constrained such that their methods of swimming as well as their sequence of strokes need to utterly satisfy the so-called scallop theorem. Considering the importance of motility for both microrobots and living creatures, this study aims to propose a model swimmer for artificial swimmers that might also be a prospective model explaining a mode of swimming for existing self-propelled natural living matters that can move forward by changing the shape of their body. The proposed swimmer is made up of three equal spheres, arranged in a triangular configuration by placing the center of each of them at the vertices of a triangle. The active links form a T-shape frame, such that the first link serves to connect two spheres, and the second link originates from the other sphere to connect it to the middle of the first link. Considering only two degrees of freedom for each link, this swimmer can translate along a straight path, by expanding or contracting its links consecutively in proper order. Obtaining the velocity of the swimmer, we study the effects of geometrical parameters of the triangle on the mean velocity of the swimmer over each cycle of motion. Finally, it will be shown that the velocity obtained here, which linearly depends on its characteristic parameters, resembles perfectly its well-known rectilinearly configured spheres counterpart, initially proposed by Najafi and Golestanian (Phys. Rev. E 69, 062901 (2004)), and its properties have been extensively studied over past years.